2015
DOI: 10.1098/rstb.2014.0142
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of immune response to typhoid and cholera vaccines

Abstract: One contribution of 15 to a discussion meeting issue 'Biological challenges to effective vaccines in the developing world'. Considerable variation in antibody response (AR) was observed among recipients of an injectable typhoid vaccine and an oral cholera vaccine. We sought to find whether polymorphisms in genes of the immune system, both innate and adaptive, were associated with the observed variation in response. For both vaccines, we were able to discover and validate several polymorphisms that were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Supportive evidence includes the intrinsic ability of S. Typhi to down-regulate its own virulence genes to facilitate evasion of human immune signaling pathways [20] and to disrupt host transcription regulation effectively disabling components of the host immune response [21]. Additionally, host characteristics, such as genetic determinants [22,23], prior pathogen exposure [24], and baseline immune cell presence [25] can lead to a muting of immune responses against S. Typhi invasion. In contrast, a murine model using S. Typhimurium has shown that immunity developed after infection does indeed offer protection from a second attack, though this relationship may be specific to the murine host or to the non-typhoid Salmonella pathogen under study [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive evidence includes the intrinsic ability of S. Typhi to down-regulate its own virulence genes to facilitate evasion of human immune signaling pathways [20] and to disrupt host transcription regulation effectively disabling components of the host immune response [21]. Additionally, host characteristics, such as genetic determinants [22,23], prior pathogen exposure [24], and baseline immune cell presence [25] can lead to a muting of immune responses against S. Typhi invasion. In contrast, a murine model using S. Typhimurium has shown that immunity developed after infection does indeed offer protection from a second attack, though this relationship may be specific to the murine host or to the non-typhoid Salmonella pathogen under study [26].…”
Section: Discussionmentioning
confidence: 99%
“…Typhi to down-regulate its own virulence genes to facilitate evasion of human immune signaling pathways [ 20 ] and to disrupt host transcription regulation effectively disabling components of the host immune response [ 21 ]. Additionally, host characteristics, such as genetic determinants [ 22 , 23 ], prior pathogen exposure [ 24 ], and baseline immune cell presence [ 25 ] can lead to a muting of immune responses against S . Typhi invasion.…”
Section: Discussionmentioning
confidence: 99%
“…"Vaccinomics" encompasses both immunogenomics and immunogenetics as it concerns immune responses to vaccine antigen. 152 The fields of personalized vaccinology and vaccinomics were the products of Phase I of the international HapMap and that of the Human Genome Project. Also, modern molecular assay techniques permitting highthroughput detection of variations at gene level, in particular linkage disequilibrium maps and single nucleotide polymorphism (SNP), played significant roles in the development of personalized vaccinology and vaccinomics.…”
Section: The Subpopulation Levelmentioning
confidence: 99%
“…It has also been shown that polymorphisms at vital immune response genes can bring about differing immune responses to biopharmaceutical products including vaccines. [152][153][154] Newer, accurate, cheap and reproducible sequencing technologies; validated databases containing genotypephenotype data; statistical and bioinformatics tools are needed in order to analyze and interpret data that will help and improve vaccine adverse and immune response quantifiability and predictability. 155 The information will enhance clinical practice and accelerate rational and directed vaccine development.…”
Section: The Subpopulation Levelmentioning
confidence: 99%
“…The potential for these studies to identify molecular mechanisms of vaccine response and implications for a personalized approach to vaccination are explored. This theme is taken up in the article from Majumder [37], which presents the findings from a study of single nucleotide polymorphisms (SNPs) in regions encoding close to 300 candidate genes and their association with antibody response following administration of injected polysaccharide typhoid vaccine or oral inactivated, whole-cell cholera vaccine. A small number of distinct SNPs are shown to be separately rstb.royalsocietypublishing.org Phil.…”
Section: Human Genetic and Environmental Determinants Of Vaccine Respmentioning
confidence: 99%